(untitled) - Bergsten, Hans (Paris, 2001)
Java Server Pages (JSP) is a new server-side technology for generating dynamic content in Web pages and other on-line applications. This guide to JSP covers all aspects of development and includes comparisons to similar dynamic content systems such as CGI, Active Server Pages, Cold Fusion, and PHP. Included is a discussion of the use of component centric design via Java Beans and custom tag libraries for separating the presentation of dynamic data (the layout, look, and feel) from its implementation.
Keywords: Trang JavaServer,JavaServer pages